2009
DOI: 10.1002/jbm.a.32530
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐induced cell signaling events control actin rearrangements and motility

Abstract: Understanding the interrelationship between material surface properties and the biological response to such materials remains a fundamental scientific challenge, as well as being of considerable practical importance in medicine. Through the use of a homologous series of copolymers of increasing hydrophobicity, we aimed to illuminate the interplay between material surface hydrophobicity and signalling events within cells in contact with this model system. Extending previous work, we hereby unravel key pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…The important role of actin fibers in maintaining cell morphology and their effect on signalling pathways monitoring several parameters such as cell death, migration and differentiation is well known [26]. Recently, the effect of NPs on focal adhesion-mediated cell signalling pathways has also been confirmed by the work of Miller et al [27] who found that depending on the nature of the NP coating, the NPs could interact more or less with the extracellular domain of integrins and thereby trigger their activation and intracellular signalling cascade. The results obtained in the present study are in line with the intracellular concentration-dependent effects as MLs and Resovist elicited the gravest effects, but were previously found to lead to the highest uptake efficiencies.…”
Section: Ionps or Cells Used And Differences In Incubation Conditionsmentioning
confidence: 88%
“…The important role of actin fibers in maintaining cell morphology and their effect on signalling pathways monitoring several parameters such as cell death, migration and differentiation is well known [26]. Recently, the effect of NPs on focal adhesion-mediated cell signalling pathways has also been confirmed by the work of Miller et al [27] who found that depending on the nature of the NP coating, the NPs could interact more or less with the extracellular domain of integrins and thereby trigger their activation and intracellular signalling cascade. The results obtained in the present study are in line with the intracellular concentration-dependent effects as MLs and Resovist elicited the gravest effects, but were previously found to lead to the highest uptake efficiencies.…”
Section: Ionps or Cells Used And Differences In Incubation Conditionsmentioning
confidence: 88%
“…[60] Myogenic differentiation is generally induced upon attaining confluence of myoblasts arranged in a highly aligned, organized manner. Therefore, scaffold biochemical cues should promote maximal adhesion and proliferation.…”
Section: Skeletal Muscle Tissue Engineering Approachesmentioning
confidence: 99%
“…Released metal ions may also lead to cytoplasmic mRNA degradation by interacting with mRNA stabilizing proteins [117], which contain metal responsive domains. NPs can interact with cellular signal molecules, which lead to signaling cascade activation [118] and induce DNA damage and cell death.…”
Section: Key Factors and Toxicity Mechanismsmentioning
confidence: 99%